Ionic and non-ionic intravenous X-ray contrast media: antibacterial agents?. (May 2022) - Mosler, Frank; Richter, Johannes K; Schindewolf, Marc; Mertineit, Nando; Tengg-Kobligk, Hendrik von; Heverhagen, Johannes T; Nöldge, Gerd
X-ray contrast media have been reported to have inhibitory effects on bacterial growth. Despite its potentially beneficial effect on patients, these features of contrast media have received relatively little attention in the medical literature in the past decades. The aim of this review is to evaluate the literature concerning the bactericidal and bacteriostatic effects of X-ray contrast media, specifically if there is a known difference concerning these effects between ionic and non-ionic contrast media. Systematic literature review was performed for the years of publication between 1911 and 2019. Since the publication of Grossich in 1911, the effect of iodine on the treatment of superficial infections in surgical procedures has been established clinical knowledge. Bacteriostatic and bactericidal effects of ionic X-ray contrast media are well established. However, non-ionic contrast agents have been the subject of little research in this respect. In past decades, the hypothesis emerged in the literature that mainly the concentration of free iodine might be responsible for any bacteriostatic or bactericidal effect of ionic X-ray contrast media. Nowadays, however, only non-ionic contrast media are used. The question regarding the mechanism and magnitude of bacteriostatic or bactericidal effects of these, non-ionic contrast media, could not be answered conclusively from this review. Non-ionic contrast media could be used intentionally when a local antibacterial effect is intended (e.g. in percutaneous abscess drainage), as well as to reduce the overall dose of antibiotics administered to a patient. Thus, this question remains relevant and might constitute the area of future research.